Belowground Carbon Dynamics in Tropical Perennial C4 Grass Agroecosystems - Crow, Susan E.; Deem, Lauren M.; Sierra, Carlos A.; Wells, Jon M. (Frontiers in Environmental Science, 2018)
Effective soil management is critical to achieving climate change mitigation in plant-based renewable energy systems, yet limitations exist in our understanding of dynamic belowground responses to the cultivation of energy crops. To better understand the belowground dynamics following cultivation of a grassland in a high-yielding tropical perennial C4 grass in a zero-tillage production system, changes in soil carbon (C) pools were quantified, modeled, and projected and the chemical composition of the aggregate-protected pool was determined. Multiple C pools with different ecosystem functions and turnover increased following cultivation: immediately available microbial substrate (measured as hot water-soluble C) and active C (determined through laboratory incubation) increased by 12% and 30% respectively over time and soil C accumulated significantly in multiple physical fractions. A more rapid and dynamic nature of multiple C pools and transfers between pools existed than is often assumed in belowground models used widely in the field to simulate soil C accumulation. Multiple indicators of fresh roots, including the more easily degraded lignin monomers and root-derived long chain substituted fatty acids, appeared in aggregate-protected pools of cultivated soils over time since planting. This rapid transfer of plant inputs through active and intermediate C pools into mineral-dominated pools is the ultimate outcome required for building soil C stocks. Initial model runs suggested that this is evident, even on a two-year frame, in transfer rates of 0.485 and 0.890 from active to slow and slow to passive pools respectively. The rapid transfer of fresh root-derived input to stable pool suggests that soil C under zero-tillage management may be resilient to disturbances, such as replanting following a kill-harvest, that would otherwise result in losses from unprotected or readily available pools.